Role of Calretinin in Determining the Aganglionic Segment in Hirschsprung's Disease - Onur Ceylan; Özgür Çağlar (Galenos Publishing House, 2020)
INTRODUCTION: This study aims to determine the presence, shape, and value of immunoreactivity of calretinin in ganglionic and aganglionic colon samples in Hirschsprung's Disease (HSCR). METHODS: This study included the ganglion positive and negative intestinal tissue materials of 63 patients admitted to the hospital with the prediagnosis of HSCR. Calretinin immunomarker was applied to the materials. The cases were divided into three groups as strongly positive, weakly positive and negative for calretinin. Staining differences between ganglionic and aganglionic tissue samples were examined. RESULTS: In all ganglionic biopsy materials, calretinin was seen to be strongly positive in the submucosal and myenteric plexuses. Calretinin was evaluated as negative in 60 of aganglionic biopsy materials whereas it was found to be weakly cytoplasmic positive in three cases. A significant difference was observed between the positive immunoreactivity of calretinin in the aganglionic and ganglionic segments (p<0.001). Rates of sensitivity, specificity, accuracy, positive, and negative predictive values were found to be 100%, 94.44%, 97.14%, 94.44%, and 100%, respectively. DISCUSSION AND CONCLUSION: Calretinin, which has high sensitivity and specificity, is extremely useful in determining ganglionic and aganglionic segments. We believe that calretinin can provide a definitive diagnosis with a single immunohistochemical study and H&E section since its interpretation is much easier compared to hematoxylin-eosin (H&E). Thus, it is extremely important in terms of reducing excessive serial sectioning, the need for immunohistochemical assay and re-biopsy